Continued administration of pembrolizumab for adenocarcinoma of the lung after the onset of fulminant type 1 diabetes mellitus as an immune‐related adverse effect: A case report. Issue 5 (9th April 2019) - Edahiro, Ryuya; Ishijima, Mikako; Kurebe, Hiroyuki; Nishida, Kohei; Uenami, Takeshi; Kanazu, Masaki; Akazawa, Yuki; Yano, Yukihiro; Mori, Masahide
Abstract : A 61‐year‐old woman with stage IVA lung adenocarcinoma exhibited high PD‐L1 expression. Pembrolizumab was administered as second‐line therapy. She developed destructive thyroiditis and her thyroid function started to decline during the administration of three to five courses. She was subsequently diagnosed with fulminant type 1 diabetes mellitus and ketoacidosis during the eighth course and insulin treatment was initiated. Pembrolizumab remained effective and was continued for 21 courses, even after the onset of diabetes mellitus. Immune‐checkpoint inhibitor treatment can be continued with hormone replacement even after the development of type 1 diabetes mellitus as an immune‐related adverse event.